eIF5A and hypusination-related disorders: literature review and case report of DOHH-related encephalopathy - Beltrán-Corbellini, Álvaro; Valls-Carbó, Adrián; Toledano, Rafael; García-Morales, Irene; Sánchez-Miranda Román, Irene; Gil-Nagel, Antonio (Journal of neurodevelopmental disorders, 2025)
Background Eukaryotic initiation factor 5 A (eIF5A) and hypusination-related disorders (eIF5A-HRD) are recently described diseases caused by pathogenic heterozygous variants in the translation factor EIF5A or biallelic variants in the two enzymes involved in the post-translational synthesis of hypusine in the eIF5A precursor, deoxyhypusine synthase (DHPS) and deoxyhypusine hydroxylase (DOHH), necessary for its activation. We review the current knowledge regarding eIF5A-HRD, and report the case of the sixth and oldest known patient with DOHH-related disorder (DOHH-D), aiming to expand and discuss the molecular basis and the general and epilepsy phenotypes of this group of diseases. Results Literature review yielded one paper describing 7 individuals with eIF5A-related disorders (eIF5A-D), one reporting 5 subjects with DHPS-related disorders (DHPS-D) and one characterizing 5 individuals with DOHH-D. Main phenotypic features consisted of prenatal issues, hypotonia, dysmorphisms, microcephaly, moderate-severe neurodevelopmental disorders/intellectual disability and behavioral disorders. We report the case of a 24-years-old male with DOHH-D manifesting as Dravet-like syndrome. He displays microcephaly and neurodevelopmental delay with attention deficit with hyperactivity disorder, along with a happy demeanor. Basic language skills and ambulation capacity with crouch gait are preserved. Onset of epilepsy was at 8 months with refractory temperature-triggered hemiclonic seizures and status epilepticus , followed by nocturnal tonic-clonic seizures from adolescence. Fenfluramine was the most effective approach, reducing seizure intensity, duration and frequency, and contributing to cognitive and behavior improvements. No patient with eIF5A-D presented seizures. Taking our patient into account, 4/5 and 4/6 reported individuals with DHPS-D and DOHH-D, respectively, presented epilepsy. Seven out of 8 epilepsy patients debuted between 2 and 5 years, most of them presented developmental and epileptic encephalopathies or generalized epilepsies (5/8 with temperature or infection-triggered seizures), and 4/8 were refractory. We hypothesize that dysregulation of IQSEC2 and SHANK3, among other genes, might contribute to the eIF5A-HRD phenotype. Conclusions eIF5A-HRD are recently described entities displaying neurodevelopmental disorders and microcephaly, and reported patients are scarce. More than 70% of DHPS-D and DOHH-D patients present epilepsy, 63% of them with temperature-triggered seizures. Valproic acid or fenfluramine may be effective. Rare homozygous or compound heterozygous missense variants in these genes should be screened in patients with encephalopathy and temperature-triggered seizures.